1997
DOI: 10.1300/j082v33n02_04
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Attitudes Toward Homosexuality in College Students

Abstract: The purpose of this study was to evaluate the implementation of a gay men and lesbian peer panel as an educational strategy in changing homophobic attitudes among 190 college students. The students were administered a modified version of the Attitudes Toward Homosexuality Scale before and after the intervention. Results indicated a significant difference between pre- and posttest scores. Men had more negative attitudes toward homosexuals than did women both before and after intervention. Suggestions for counse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 20 publications
3
63
0
Order By: Relevance
“…I think it was a really hard decision for him to come to.'' Consistent with research demonstrating that positive interactions with LG individuals (Lance 1987) and exposure to LG peer speaker panels (Nelson and Krieger 1997) are related to reductions in negative attitudes toward LG persons, these participants attributed their affirmative reactions to exposure to LG persons and/or early exposure to LG affirmative educational experiences, and, for one participant, having a lesbian mom. One participant stated, I had already met a lot of people and become friends with a lot of people, gay and lesbian and I was very comfortable in that environment.…”
Section: Happiness and Acceptancesupporting
confidence: 65%
“…I think it was a really hard decision for him to come to.'' Consistent with research demonstrating that positive interactions with LG individuals (Lance 1987) and exposure to LG peer speaker panels (Nelson and Krieger 1997) are related to reductions in negative attitudes toward LG persons, these participants attributed their affirmative reactions to exposure to LG persons and/or early exposure to LG affirmative educational experiences, and, for one participant, having a lesbian mom. One participant stated, I had already met a lot of people and become friends with a lot of people, gay and lesbian and I was very comfortable in that environment.…”
Section: Happiness and Acceptancesupporting
confidence: 65%
“…Trainers may consider using a variety of teaching modalities. For instance, Croteau and Kusek (1992) and Nelson and Krieger (1997) have found evidence of effectiveness for the use of panel presentations to reduce homophobia in students. Although not designed to provide therapy training, the panels so serve to introduce students to LGB people and the issues associated with these sexual orientations.…”
Section: Individual and Cultural-diversity Competencymentioning
confidence: 99%
“…The current study builds upon the work of Athanases and Larrabee (2003), Ben-Ari (1998), Nelson and Krieger (1997), and others who have provided insights into students' responses to instruction on lesbian and gay issues. While the most recent study by Athanases and Larrabee was conducted in California, (inter)nationally recognized for its progressive stance toward the LGBT community, this study was conducted in a Midwestern state that lacks both statemandated legal protections for LGBT people in employment and housing and a statewide anti-bullying education policy that specifically protects LGBT students.…”
Section: Discussionmentioning
confidence: 99%
“…In efforts to mitigate sexual prejudice, instructors have invited LGBT people to speak to their classes about their experiences. Analysis of 190 college students' responses following a peer panel presentation by lesbian and gay students demonstrated positive attitudinal changes; the authors identified an interactive encounter and elicitation of feedback from participants following the discussion as essential factors for bringing about positive attitudinal shifts (Nelson & Krieger, 1997).…”
Section: Introductionmentioning
confidence: 99%